KEJADIAN DBDDI KELURAHAN MANISREJO KECAMATAN TAMAN KOTA MADIUN TAHUN 2015 - Firda Lutfi Pangresti; Tuhu Pinardi; Hery Koesmantoro (Poltekkes Kemenkes Surabaya, 2016)
Manisrejo village incidence of dengue fever is the highest among the City of Madiun. Thenumber of cases of dengue hemorrhagic fever in that village was as many as 84 cases in2010-2014. This study aims to find out about the incidence of dengue fever. By measuringbehavioral factors, assess physical factors, calculating factor-free numbers larva, evaluate PSN(mosquito nest eradication), evaluates health services, measuring the socio-economic factors,and to describe the incidence of dengue fever. This type of research is a descriptive study. Populations were all cases of dengue fever inthe village Manisrejo District of the City of Madiun. The sample is purposive sampling counted84 cases and the controls. The results generated from the calculation of questionnaires and observation done. It isknown that most of the respondents behavior is bad namely 87.8%, physical factors such astemperature and humidity most of the houses of the respondents have optimum temperatureand humidity which is a mosquito breeding sites by 83.67%. Village ofManisrejois still not freefrom larvae, this is because free larva houseswere still below 95%, the mosquito eradicationis bad that is equal to 59.2%, patients with dengue fever in the village Manisrejo utilize healthservices and are willing to seek treatment when exposed to pain, patients with dengue feverat most households were not poor 84,7%. It is recommended to the citizens in order to improve the attitudes and actions ofmosquito control, as well as the mobilization of mosquito eradication movement cadres inparticular for monitoring larvae, as well as public attention to environmental conditions suchas opening a window or vent, this can help to regulate the temperature and humidity.